The Characteristics of Natural Killer Cells and T Cells Vary With the Natural History of Chronic Hepatitis B in Children - Zhou, Yingzhi; He, Yi; Chang, Yunan; Peng, Xiaorong; Zhao, Ruiqiu; Peng, Mingli; Hu, Peng; Ren, Hong; Chen, Min; Xu, Hongmei (Frontiers in Pediatrics, 2021)
Background and aims: The immune status of chronic hepatitis B(CHB) children in different phases were still unclear. The aim of this study is to investigate the phenotype and cytokine producing ability of natural killer (NK) and T cells and better understand the immune characteristics of different phases in CHB children. Methods: Treatment naive CHB children were divided into different clinical phases of CHB. Fresh drawn peripheral blood from HBV-infected and healthy children was processed to perform flow cytometry analysis. Results: A total of 112 treatment naive CHB children and 16 comparable healthy controls were included in the this study. Compared with healthy controls, the expression of HLA-DR on NK cells and CD38 on T cells in CHB children were upregulated, especially in IA phase. The ability of circulating NK cells instead of CD8+ T cells to produce IFN-γ in CHB children was slightly increased, but the ability of TNF-α production seemed to decrease compared to healthy controls. Some activation markers varied among different phases of CHB children especially higher CD38 expression on T cells in IA phases. Regression analysis revealed that IFN-γand TNF-α production of NK cell and CD8+T cells seemed to have a positive correlation with ALT elevation and activated status of NK cells or T cells. Conclusion: NK cells and T cells tended to be phenotypic activated (especially in IA phase) in CHB children compared to healthy control. But their cytokine-producing function were not obviously elevated especially IFN-γproduction from CD8+T cells. More studies investigating the mechanism and observing the longitude change of the immune status in CHB children are needed.